Guest Editors' Introduction:Corporate Sustainability Management and Environmental Ethics. Issue 2 (11th April 2017) - Schuler, Douglas; Rasche, Andreas; Etzion, Dror; Newton, Lisa
ABSTRACT: This article reviews four key orientations in environmental ethics that range from an instrumental understanding of sustainability to one that acknowledges the intrinsic value of sustainable behavior (i.e., sustainable resource use, conservation and preservation, rights-based perspectives, and deep ecology). It then shows that the current scholarly discourse around corporate sustainability management—as reflected in environment management (EM), corporate social responsibility (CSR), and corporate political activity (CPA)—mostly favors an instrumental perspective on sustainability. Sustainable business practices are viewed as anthropocentric and are conceptualized as a means to achieve competitive advantage. Based on these observations, we speculate about what corporate sustainability management might look like if it applied ethical orientations that emphasize the intrinsic value of nature. This discussion also includes an introduction to two articles in this special section focused on the role of the environmental manager and sustainability standards, both of which offer paths for incorporating intrinsic valuation of the environment into sustainability management.